Characteristics of Ti and Fe doped LiCo0.6Ni0.4O2 cathode materials for Li-ion rechargeable batteries. (3rd April 2017) - Kamarulzaman, Norlida; Azahidi, Azira; Elong, Kelimah; Kasim, Muhd Firdaus; Rusdi, Roshidah; Mokhtar, Nurul Atikah Mohd; Aziz, Nor Diyana Abd; Osman, Zurina
Abstract: Partial substitution of Fe and Ti was done to replace Co in LiCo0.6 Ni0.4 O2 cathode materials producing LiCo0.55 Ni0.4 Ti0.05 O2 and LiCo0.55 Ni0.4 Fe0.05 O2 novel stoichiometries and improved behaviour of the materials. The materials were prepared by using a self-propagating combustion method. The materials are found to be single phase and pure of the hexagonal structure and R 3 ¯ m space group. Results showed that the doped materials perform better than the undoped material and Ti substituted material performs better than the Fe substituted material in terms of first cycle capacity and capacity retention. To further understand the effect of structure and electrochemical behaviour of the materials, quantitative structural studies of the materials were done via x-ray diffraction (XRD) and using the Rietveld refinement method. It was found that the Fe and Ti doped materials had larger lattice parameters implying greater inter-layer spacings and therefore, increased ease for the movement of the Li + ions through the layered structures which explained the improved performance of the electrochemical cells. Binding energy and oxidation state studies of the transition metals were also done via x-ray photoelectron spectroscopy (XPS) and results showed that lithium was more tightly bound in the structure of the undoped LiCo0.6 Ni0.4 O2 material agreeing with the XRD structural studies of bond length. Results were also supported by conductivity studies that showed that the Ti substituted material had the highest conductivity.